Wawasan Kebersihan Lingkungan & Keberagamaan; Praktik Kebersihan Lingkungan pada Civitas Akademika UIN Imam Bonjol Padang - Rulan Permata Sari (Indonesian Center for Religion and Society Studies (InTReSt), 2019)
The basic identity of academic community of UIN Imam Bonjol Padang is Muslim, with sufficient religious knowledge. This study aims to see the correlation of knowledge with behavior in maintaining environmental cleanliness. The research data collection was carried out by survey and in-depth interviews with the academic community of UIN Imam Bonjol. This study found that, first the understanding of the academic community of UIN Imam Bonjol Padang about cleanliness was quite good at the individual level originating from the hadith about cleanliness, both in text and in substance. Second, in maintaining cleanliness, UIN academics are influenced by the lack of available hygiene facilities and infrastructure and the absence of regulation. Third, there is an asymmetrical relationship between the knowledge of the UIN academic community about environmental hygiene and practice because the understanding of environmental hygiene is still in the domestic area and is private in nature, not yet entering the public space.